Mesenchymal Stem Cells with Simultaneous Overexpression of GPX3 and CD47 for the Treatment of Drug-Induced Acute Liver Injury - Yuanxiang Jing; Balun Li; Aili Aierken; Zengyu Zhang; Dongyao Han; Zixi Lin; Jiaqi Gao; Hongkai Tian; Jinlian Hua (Veterinary Sciences)
The liver, as the largest metabolic and detoxification organ in mammals, metabolizes approximately 80–90% of drugs. However, drug-induced liver injury (DILI) is common and driven by factors such as individual variability, differences in liver metabolism, and improper drug use. Mesenchymal stem cells (MSCs), with their self-renewal and multipotent differentiation capabilities, offer therapeutic potential, but face challenges such as limited proliferation and increased apoptosis during in vitro expansion. Although MSCs exhibit low immunogenicity, they are often cleared by the host immune system, which limits their survival and engraftment. Glutathione peroxidase 3 (GPX3) is a key antioxidant enzyme that reduces reactive oxygen species (ROS), protecting cells from oxidative damage. CD47, also known as integrin-associated protein (IAP), helps cells evade immune clearance by binding to signal regulatory protein alpha (SIRPα) on the immune cells. Here, we used an acetaminophen (APAP)-induced DILI mouse model to evaluate the therapeutic efficacy of intravenously infused MSCs overexpressing GPX3 and CD47. Compared to unmodified MSCs, modified MSCs showed improved survival, reduced liver inflammation, and alleviated oxidative damage, offering enhanced protection against APAP-induced DILI.